2 - Developmental Local Government in Post-Apartheid South Africa? A Feminist Rethinking of the State and Development in the Context of Neo-liberalism - Samson, Melanie (Africa Development, 2007)
Neoliberal dictates and structural adjustment policies have denuded African states and attempted to limit their role to enabling the building and functioning of markets. These policies have failed to promote development, exacerbated gender inequities, and deepened Africa’s entanglement within exploitative imperialist economic relations. There is, therefore, a pressing need to re-establish a proactive, developmental role for the state in Africa. This article argues that in the current conjuncture such a project must be grounded in a radical reconceptualisation of both development and the state. Previous statist theo- ries of development erred in casting development as a set of outcomes to be delivered by the state to a passive population. Due to their inattentiveness to gender they also reproduced and exacerbated exploitative gender relations. The article argues that in a context where it is difficult to even imagine an alternative to neoliberalism, development should be redefined as building collective capac- ity to envision, create and struggle for a society and economy free of gender, racial and class exploitation. The state must be reconfigured so that it is both strengthened by and helps to build collective capacity through processes of participatory democracy attentive to addressing and overcoming the mutually constituting structural inequalities of gender, race and class. Amidst the continent-wide retreat of the state from an active role in the development process, the post-apartheid South African policy of ‘developmen- tal local government’ would seem to be grounded in just such a retheorization of the state and development. The policy establishes that the local government must promote development, redress apartheid inequalities and be participatory and gender sensitive. The article argues however that the South African ap- proach is compromised by three fundamental weaknesses at the level of policy formulation. These pertain to the liberal conceptualisation of participation, the reduction of commitments to gender transformation to a focus on the participa- tion of women, and the endorsement of a contracting vision for the local state which eliminates an active role for either the state or the citizenry in the develop- ment process. The article concludes by exploring more successful attempts at gender transformative, participatory approaches to governance and development in other parts of the world and reflecting on the challenges to pursuing them in the South African context.